Sensation-seeking hedge funds - BROWN, Stephen (Institutional Knowledge at Singapore Management University, 2017)
Using a novel dataset of hedge fund manager automobile purchases, we show that, motivated by sensation seeking, hedge fund managers often take risk for personal and non-pecuniary reasons. In line with the sensation seeking view, managers who own powerful sports cars take on more investment risk but do not deliver higher returns, resulting in lower Sharpe ratios. Moreover, funds managed by performance car owners exhibit higher operational risk and are more likely to fail. Performance car owners demonstrate other attributes associated with sensation seeking, such as a preference for lottery-like stocks, unconventional strategies, and active trading.